Highly Efficient and Stable FA-Based Quasi-2D Ruddlesden-Popper Perovskite Solar Cells by the Incorporation of β-Fluorophenylethanamine Cations - Zhang, Yunxin (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.